1986
DOI: 10.1007/bf00286730
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various dietary fibres on tissue concentration and chemical form of mercury after methylmercury exposure in mice

Abstract: The whole-body retention of mercury after exposure of BALB/c mice to methylmercury was measured in animals fed fibre-free, 5% pectin, 5% cellulose or 5, 15 or 30% wheat bran diets. The rate of elimination of mercury was dependent on the diet fed, with dietary bran increasing the rate of elimination. The incorporation of 15 or 30% bran in the diet of the mice decreased the total mercury concentration in the brain, blood and small intestine, although the effects were significant only in those animals on 30% bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 24 publications
3
35
0
4
Order By: Relevance
“…Accordingly, earlier studies have demonstrated identical halftimes of methylmercury in mice exposed intraperitoneally and in mice fed a diet with CH 3 HgCI added (Clarkson, 1972). However, the available information on intestinal uptake of orally administered methylmercury in experimental animals is limited, and divergent figures for the wholebody retention of mercury at similar periods after dosage to mice have appeared (Clarkson, 1972;Landry et al, 1979;Mehra and Kanwar, 1980;Rowland et al, 1986). Furthermore, differences between retention of orally and intraperitoneally administered methylmercury have been reported (Mehra and Kanwar, 1980).…”
Section: Toxicokinetics Of Methylmercury In Experimental Animalsmentioning
confidence: 88%
“…Accordingly, earlier studies have demonstrated identical halftimes of methylmercury in mice exposed intraperitoneally and in mice fed a diet with CH 3 HgCI added (Clarkson, 1972). However, the available information on intestinal uptake of orally administered methylmercury in experimental animals is limited, and divergent figures for the wholebody retention of mercury at similar periods after dosage to mice have appeared (Clarkson, 1972;Landry et al, 1979;Mehra and Kanwar, 1980;Rowland et al, 1986). Furthermore, differences between retention of orally and intraperitoneally administered methylmercury have been reported (Mehra and Kanwar, 1980).…”
Section: Toxicokinetics Of Methylmercury In Experimental Animalsmentioning
confidence: 88%
“…Diets are important modulators of MeHg absorption (Chapman and Chan, 2000). Mice fed a high fiber diet (as 30% wheat bran) accumulated less THg in the small intestine, brain and blood compared to mice fed fiber-free and low-fiber diets, and the authors attributed this to differences in the metabolic activity of gut microbiota (Rowland et al, 1986). Among Brazilian fishers, the strength of the relationship between average hair Hg levels and fish consumption was weaker for those consuming at least one piece of fruit per day, and the authors suggested this may be due to the soluble dietary fiber content or other prebiotic nutrients of fruits, which modified the absorption of MeHg from the gut (Passos et al, 2003, 2007).…”
Section: Comprehensive Inventory Of Rice Grain Thg and Mehg Concenmentioning
confidence: 99%
“…The ability of pectin to reduce absorption and the bioaccumulation of toxic metals is attributed to pectin binding the metals in the digestive tract and preventing their absorption while facilitating their elimination in the feces. This may also include metals that have been absorbed previously and have been excreted into the bile or undergone enterohepatic circulation (Niculescu et al, 1969;Rowland et al, 1986).…”
Section: Introductionmentioning
confidence: 98%